2023
DOI: 10.1186/s12883-022-03014-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of decompressive craniectomy in acute ischemic stroke patients treated with intravenous thrombolysis

Abstract: Introduction The optimal timing for decompressive hemicraniectomy (DHC) after intravenous thrombolysis (IVT) remains unclear. This study in patients with acute ischemic stroke treated with IVT aimed to assess the safety of DHC and patient outcome. Methods Data was extracted from the Tabriz stroke registry from June 2011 up to September 2020. In all, 881 patients were treated with IVT. Among these, 23 patients underwent DH. Six patients were exclude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…While the impact of DH on outcomes following malignant middle cerebral artery infarction (mMCAi) remains a subject of debate, there is a dearth of literature that reports on its effects after posterior vascular strokes. In one study of DH after IVT, no patient over 60 years old survived to 3-month follow-up, and moderate disability at 3 months was present in 35.5% 51 . Inamasu et al showed that despite the absence of differences in any of the demographic variables evaluated, the mortality rate was significantly higher in the group of individuals over 70 years old who underwent DH compared to those aged 61–70 52 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While the impact of DH on outcomes following malignant middle cerebral artery infarction (mMCAi) remains a subject of debate, there is a dearth of literature that reports on its effects after posterior vascular strokes. In one study of DH after IVT, no patient over 60 years old survived to 3-month follow-up, and moderate disability at 3 months was present in 35.5% 51 . Inamasu et al showed that despite the absence of differences in any of the demographic variables evaluated, the mortality rate was significantly higher in the group of individuals over 70 years old who underwent DH compared to those aged 61–70 52 .…”
Section: Discussionmentioning
confidence: 98%
“…Thirdly, NIHSS Scale was utilized to evaluate the clinical condition of patients undergoing AMT and PMT procedures. It is worth noting that the NIHSS scale may not comprehensively capture the severity of the clinical condition in patients with posterior circulation stroke 51 . Fourthly, our study primarily relied on the clinical status of patients at discharge and on the 90th day after the procedure, whereas some investigations extend their focus to outcomes after one year.…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of DH on outcomes following malignant middle cerebral artery infarction (mMCAi) remains a subject of debate, there is a dearth of literature reports on its effects after posterior vascular strokes. In one study of DH after IVT, no patient over 60 years old survived to 3-month follow-up, and moderate disability at 3 months was present in 35.5% 49 .…”
Section: Factors Related With After Mtmentioning
confidence: 98%